Strategi Komunikasi Pemasaran dalam Mempertahankan Customer Loyalty pada Hotel Salak Bogor, Indonesia - Farida Hariyati; Rina Sovianti (Fakultas Ilmu Komunikasi Universitas Pancasila, 2021)
Hospitality industry is an integral part of the tourism sector in Indonesia. This study aims to examine the marketing communication strategy of Hotel Salak The Heritage in maintaining customer loyalty in the city of Bogor, as one of the major tourism cities in Indonesia, amidst the presence of new hotels that have increased significantly. This study used a qualitative approach with descriptive methods. Data analysis was carried out with triangulation techniques to confirm the results of in-depth interviews related to findings in the field. The results of this study reveal that marketing communication strategies in maintaining customer loyalty are carried out in harmony with the cultural identity inherent in this hotel. HSTH was designated as a cultural preserve by the local government of Bogor. The use of technology becomes the concern for the public relations and marketing division of HSTH to design and process messages through various social media, non-media promotions, and artificial intelligent.